Serangan Hama Siput Darat (Bradybaena similaris) pada Pertanaman Kubis (Brassica oleracea var. capitata) di Wilayah Kecamatan Karangreja, Kabupaten Purbalingga - Margaretha Butarbutar; R. Rostaman (Pro-Life, 2024)
Cabbage (Brassica oleracea capitata) is an important commodity in the Karangreja area of Purbalingga District. The crop is attacked by land snails. The objectives of this study were to: 1) identify the land snail species that attack cabbage crops; 2) ascertain the snail attack symptoms; 3) ascertain the snail population and attack intensity; and 4) show where snails are found in cabbage fields. The Purbalingga Regency's Karangreja Sub-district served as the site of the survey investigation. The Indonesian Institute of Sciences' Research Center of Biology, Laboratory of Zoology, identified land snails. The study was from February until April 2017. The findings indicated that Bradybaena similaris was a species of land snail. The snail attack was characterized by circular holes in the center of the leaves. The snail population ranged from 8.21 to 44.90 individuals, with varying assault intensities of low (21-40%) and medium (41-60%). The snail is distributed in a clumped pattern. We concluded that Bradybaena similaris snails are an important pest of cabbage plants.